Source matrices used to obtain the trophic and spatial seed dispersal networks - Rumeu, Beatriz; Donoso, Isabel; Rodríguez-Pérez, Javier; García, Daniel (Dryad, 2020)
1. Trophic relationships have inherent spatial dimensions associated with
the sites where species interactions, or their delayed effects, occur.
Trophic networks among interacting species may thus be coupled with
spatial networks linking species and habitats whereby animals connect
patches across the landscape thanks to their high mobility. This trophic
and spatial duality is especially inherent in processes like seed
dispersal by animals, where frugivores consume fruit species and deposit
seeds across habitats. 2. We analysed the frugivore-plant interactions and
seed deposition patterns of a diverse assemblage of frugivores in a
heterogeneous landscape in order to determine whether the roles of
frugivores in network topology are correlated across trophic and spatial
networks of seed dispersal. 3. We recorded fruit consumption and seed
deposition by birds and mammals during two years in the Cantabrian Range
(N Spain). We then constructed two networks of trophic (i.e.
frugivore-plant) and spatial (i.e. frugivore-seed deposition habitat)
interactions and estimated the contributions of each frugivore species to
the network structure in terms of nestedness, modularity and complementary
specialization. We tested whether the structural role of frugivore species
was correlated across the trophic and spatial networks, and evaluated the
influence of each frugivore abundance and body mass in that relationship.
4. Both the trophic and the spatial networks were modular and specialized.
Trophic modules matched medium-sized birds with fleshy-fruited trees, and
small bird and mammals with small-fruit trees and shrubs. Spatial modules
associated birds with woody canopies, and mammals with open habitats.
Frugivore species maintained their structural role across the trophic and
spatial networks of seed dispersal, even after accounting for frugivore
abundance and body mass. 5. The modularity found in our system points to
complementarity between birds and mammals in the seed dispersal process, a
fact that may trigger landscape-scale secondary succession. Our results
open up the possibility of predicting the consumption pattern of a diverse
frugivore community, and its ecological consequences, from the uneven
distribution of fleshy-fruit resources in the landscape.